The Use of Song to Improve Students' Listening Skill of Ninth Grade at SMPN 1 Jember - Hafid Hafid; Ela Nur Laili (BATARA DIDI : English Language Journal, 2023)
This study investigated the development of students' listening abilities through songs and lyrics and explored the students’ responses toward the use of songs and lyrics in the classroom as a learning media. It was aimed at looking for the best strategy used in the listening class to help students easily mastering English language. This study was conducted through classroom action research and employed pre-test, post-test, observation, questionnaire, and interview to collect the data. The data in this study were analysed by using quantitative and qualitative descriptive. This classroom action research was conducted in two cycles. The quantitatively obtained data in the first cycle showed that mean is about 80 which mean that there was an improvement but was not significant from the pre-cycle because the grammar focus was uncovered. Meanwhile, the data in the second cycle showed that the mean is about 87; it showed the significant increase and successful process of learning throughout songs and lyrics. Furthermore, the qualitative data demonstrated 84% which means that the use of songs and lyrics in the classroom was attractive and joyful to be applied in the classroom as a learning media.